1977
DOI: 10.2165/00003088-197702030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Serum Digoxin Concentration

Abstract: Significant problems exist in the interpretation of serum digoxin concentration data. Failure to distinguish between results that do not require precise clinical correlation (proof of absorption, presence of drug, etc) and those which depend upon clinical correlation for their meaning ('toxicity' or 'effectiveness') can result in interpretive errors. Problems relating to the source of the serum digoxin concentration can also confound interpretation. Such difficulty may be controllable (obtaining the sample at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In contrast, these results in healthy volunteers do not rule out the possibility of an interaction under conditions in which digoxin pharmacokinetics would be modified such as oedema of decompensated heart failure, organic or functional renal failure, or the concomitant prescription of drugs which modify digoxin pharmacokinetics (some antiarrhythmics, in particular quinidines, and calcium antagonists) (Doherty & Perkins, 1962;Weintraub, 1983).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, these results in healthy volunteers do not rule out the possibility of an interaction under conditions in which digoxin pharmacokinetics would be modified such as oedema of decompensated heart failure, organic or functional renal failure, or the concomitant prescription of drugs which modify digoxin pharmacokinetics (some antiarrhythmics, in particular quinidines, and calcium antagonists) (Doherty & Perkins, 1962;Weintraub, 1983).…”
Section: Discussionmentioning
confidence: 85%
“…The radioimmunoassay of digoxin was not affected by the presence of cicloprolol. The percentage recovery of digoxin was 86% with a precision and reproducibility that was normal for a radioimmunoassay (Smith et al, 1969;Weintraub, 1983).…”
Section: Pharmacokinetic Studymentioning
confidence: 80%
“…Advanced heart disease, acute and chronic pulmonary disease and impaired atrioventricular conduction all increase the risk of cardiotoxicity (Beller et aI., 1971;Fogelman et aI., 1971;Smith and Haber, 1970) and the need for regular reassessment. See further, recent reviews in the journal (Greenblatt et aI., 1976;Iisalo, 1977;Rane and Wilson, 1976;Weintraub, 1977;Wettrell and Andersson, 1977).…”
Section: Follow-up Of Patients Receiving Maintenance Digoxinmentioning
confidence: 99%
“…In animal studies, digoxin distribution in the myocardium has been shown to be affected in different ways by a variety of pathological factors, including ischaemia or changes in blood flow to various portions of the heart (Beller et aI., 1972;Hopkins et aI., 1973), electrolyte disturbances (Binnion and Morgan, 1971;Harrison and Wakim, 1969;Marcus et aI., 1969), combined hypoxia and hypercapnia (du Souich et aI., 1985a), but not isolated hypoxia (du Souich et aI., 1985b). The distribution of digoxin appears to be altered also in thyroid disease (Aronson, 1980b) and in renal failure (Aronson and Orahame-Smith, 1976;Weintraub, 1977). Impairment in renal function, for example, is associated with a reduced volume of distribution and lower tissue binding -a strong positive correlation between myocardium/serum digoxin concentration ratios and estimated premorbid creatinine clearance has 507 been described in digoxin-treated patients studied at autopsy (Jusko and Weintraub, 1974).…”
Section: Disease-induced Alteration In Tissue Distributionmentioning
confidence: 99%